Early Childhood Education Teachers' Strategies in Managing Hyperactive Behavior in Early Childhood Education Through an Islamic Education Approach in Rebang Tangkas Village Kindergarten, Way Kanan - Aniyawati Aniyawati; Nurfaizah Nurfaizah (PT. Anagata Sembagi Education, 2026)
This study aims to describe the strategies of early childhood education teachers in managing hyperactive behavior in early childhood through an Islamic educational approach, particularly in rural communities. Hyperactive behavior characterized by excessive motor activity, impulsivity, and difficulty concentrating presents a serious challenge in the learning process in early childhood education institutions. Given the limited professional resources in rural areas, an Islamic approach is a strategic alternative because it offers moral and spiritual values that can be internalized from an early age. This study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the strategies employed by teachers included habituating religious activities such as daily prayer and listening to stories of the Prophet, implementing role models (uswah hasanah), reinforcing positive routines, and close collaboration with parents. This approach was deemed effective in reducing symptoms of hyperactivity and fostering children's self-awareness of appropriate behavior. These findings recommend the need to strengthen the capacity of early childhood education teachers through inclusive Islamic education-based training and developing a curriculum that adapts to the needs of hyperactive children.